The surprises in optical coherence tomography (OCT) findings in patients presenting with in-stent restenosis: the road less travelled. (25th January 2023) - Roy, S; Singh, V; Ahmed, J; Dwivedi, S K; Sethi, R; Chandra, S; Pradhan, A K; Vishwakarma, P; Sharma, A K; Bhandari, M; Shukla, A; Singh, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Morphological features of neointimal tissue play a pivotal role in the pathophysiology of In-Stent Restenosis (ISR) after percutaneous coronary intervention, hence understanding these features and patterns is crucial. Purpose: The present study was designed to qualitatively and quantitatively assess neointimal characteristics of lesions using OCT in patients presenting with ISR. Methods: This was a single-center, prospective, observational study performed between 1st August 2020 and 30th December 2021 at a tertiary-care center in India. Patients diagnosed with stable angina and acute coronary syndrome with post-procedural angiographically documented restenosis (>50%) were included. Qualitative and quantitative assessment of neointimal hyperplasia patterns was performed using OCT. Results: A total of 34 patients with ISR were studied. Neointimal hyperplasia was classified as (i) homogenous group (n=18) and (ii) non-homogenous group (n=16). As many as 14 (77.8%) diabetics belonged to the homogenous group. Predominant plaque characteristics such as neoatherosclerosis, cholesterol crystals, and calcium were documented in 14 (77.8%), 12 (66.7%), and 11 (61.1%) patients in the homogenous group and in 10 (62.5%), 10 (62.5%), and 9 (56.2%) patients in the non-homogenous group, respectively. Unexpanded stent struts were identified in 11 (61.1%) and 11 (68.8%) patients in the homogenous and non-homogenous groups, respectively. Mean strut thickness was 93.73 ± 31.03 µm and 83.54 ± 18.0 µm, ISR was 72.50 ± 15.93% and 65.37 ± 21.69%, the neointimal thickness was 588.06 ± 167.82 mm and 666.25 ± 218.05 mm, and neointimal hyperplasia was 54.54 ± 11.23% and 59.26 ± 8.86% in the homogenous and non-homogenous groups, respectively. Conclusion: Neoatherosclerosis and stent underexpansion was predominantly observed in our study, which was in contrast to most of the existing literature [1, 2, 3], and only diabetes was found to be significantly associated with homogenous neointimal hyperplasia, irrespective of the generation of the stent.